Carbon-fluid equilibria and the oxidation state of the upper mantle - Blundy, J; Brodholt, J; Wood, B (1991)
IT has been proposed that the oxidation state of the Earth's upper mantle is buffered by C-O fluids in equilibrium with elemental carbon1,2. A large body of data on the oxygen fugacities (fo2) recorded by mantle rocks and their derivative melts now allows us to test this proposal. By comparing the measured fo2 values with those calculated for carbon-CO2-CO-carbonate equilibria along appropriate mantle geotherms, we find the data to be wholly consistent with this hypothesis. Moreover, the calculated variation of fo2 with temperature and pressure accounts for much of the observed correlation between the oxidation state of mantle samples and their tectonic provenance3,4. The apparent buffering of mantle fo2 requires modest quantities of mantle carbon and fluid, which do not exceed independently estimated values. The proposal is not compromised if parts of the mantle are fluid-undersaturated, or if the C-O fluid phase is diluted by other volatiles.